2014
DOI: 10.3109/09687637.2014.918089
|View full text |Cite
|
Sign up to set email alerts
|

How should we measure addiction recovery? Analysis of service provider perspectives using online Delphi groups

Abstract: Aim s: To explore ways of measuring addiction recovery and the extent of agreement/disagreement between diverse service providers on potential recovery indicators. Methods: Separate online Delphi groups with (i) addiction psychiatrists (n = 10); (ii) senior resi dential rehabilitation staff (n = 9); and (iii) senior inpatient detoxification unit staff (n = 6). Each group was conducted by email and followed the same structured format involving three iterative rounds of data collection. Content analyses were und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 16 publications
(15 reference statements)
4
75
0
Order By: Relevance
“…Our recent experiences of developing a PROM for addiction recovery, with significant service user involvement and combining qualitative and quantitative methods, have been illuminating in this respect (Neale et al, 2014(Neale et al, , 2015. First, we found that service users routinely disagreed on many aspects of the PROM content, particularly the questions to be included and terminology to be used.…”
mentioning
confidence: 92%
“…Our recent experiences of developing a PROM for addiction recovery, with significant service user involvement and combining qualitative and quantitative methods, have been illuminating in this respect (Neale et al, 2014(Neale et al, , 2015. First, we found that service users routinely disagreed on many aspects of the PROM content, particularly the questions to be included and terminology to be used.…”
mentioning
confidence: 92%
“…'Recovery' is described frequently as a complex and contested concept [6] which eschews definition [3]. Despite the contentious debate, there has been increasing agreement that 'recovery' means more than abstinence or reduction in substance use, and should encompass improvements in other areas of clients' lives, including housing, relationships, employment, participation and wellbeing [6,7].However, as the work of Neale and colleagues [7][8][9] has shown, conceptualizing, defining and measuring the broad set of outcomes that might constitute 'recovery' is not without its challenges. Recognizing that clinicians and clients may differ in their understandings of 'recovery' and in their assessment of the relative importance of specific outcomes would appear to be essential.…”
mentioning
confidence: 99%
“…'Recovery' is described frequently as a complex and contested concept [6] which eschews definition [3]. Despite the contentious debate, there has been increasing agreement that 'recovery' means more than abstinence or reduction in substance use, and should encompass improvements in other areas of clients' lives, including housing, relationships, employment, participation and wellbeing [6,7].…”
mentioning
confidence: 99%
See 2 more Smart Citations